Gemcitabine plus carboplatin versus gemcitabine plus oxaliplatin in cisplatin-unfit patients with advanced urothelial carcinoma: a randomised phase II study (COACH, KCSG GU10-16). (March 2020) - Park, Inkeun; Kim, Bong-Seog; Lim, Ho Yeong; Kim, Hee-Jun; Lee, Hyo Jin; Choi, Yoon Ji; Park, Kyong Hwa; Lee, Kyung Hee; Yoon, Shinkyo; Hong, Bumsik; Hong, Jun Hyuk; Ahn, Hanjong; et al.
Abstract: Purpose: Gemcitabine–oxaliplatin (GEMOX) demonstrated mild toxicity and promising effectiveness in patients with advanced urothelial cell cancer (UCC). We investigated the activity and safety of first-line GEMOX compared with gemcitabine–carboplatin (GCb) in cisplatin-ineligible patients with advanced UCC. Methods: Treatment-naive, cisplatin-ineligible patients with advanced UCC were randomly assigned to GEMOX (gemcitabine 1000 mg/m 2, oxaliplatin 100 mg/m 2 on day 1 [D1] every 2 weeks) or GCb (1000 mg/m 2 of gemcitabine on D1 and D8 and carboplatin area under the curve of 4.5 mg/mL/min on D1 every 3 weeks). We evaluated the objective response rate (ORR), progression-free survival (PFS) and overall survival (OS). Results: Between January 2011 and March 2017, 80 patients were enrolled; 39 and 40 patients were allocated to GCb and GEMOX arms, respectively. The ORR was 48.7% in the GCb arm and 55.0% in the GEMOX arm. The median follow-up duration was 37.8 months; the median PFS and OS in the GCb and GEMOX arms were 5.5 months (95% confidence interval [CI], 4.8–6.2) vs. 4.4 months (95% CI, 2.7–6.1) and 9.1 months (95% CI, 5.2–13.0) vs. 11.0 months (95% CI, 6.9–15.0), respectively. ≥ Leucopenia, neutropenia and fatigue of ≥ grade III were significantly more common in the GCb arm (26% vs. 3%, P  = 0.003; 33% vs. 10%, P  = 0.014; 15% vs. 3%, P  = 0.012), whereas any-grade neuropathy was more common in the GEMOX arm (8% vs. 60%). Conclusions: GEMOX showed similar efficacy with GCb and a favourable haematologic toxicity profile. GEMOX may be an additional chemotherapy option for patients with UCC ineligible for cisplatin-containing chemotherapy (NCT01487915). Highlights: Gemcitabine/carboplatin and gemcitabine/oxaliplatin had similar efficacy. The toxicity profile differed between the two regimens. Haematological toxicities and fatigue were more common in the gemcitabine/carboplatin arm. Peripheral sensory neuropathy was more common in the gemcitabine/oxaliplatin arm.